An overview of wireless transmission technology utilizing artificial intelligence - Jing ZHANG; Shi JIN; Chaokai WEN; Feifei GAO; Tao JIANG (Dianxin kexue, 2018)
Intelligent communication is considered to be one of themainstream directions in the development of wireless communications after 5G.Its basic idea is to introduce artificial intelligence into all aspects of wireless communication systems,realizing the significant integration of wireless communication and artificial intelligence technology.At present,the research in this field is advancing to the physi cal layer.The combination of wireless transmission and deep learning is also in the preliminary exploration stage.Key technologies of wireless physi cal layer based on deep learning were introduced in detail from the aspects of channel estimation,signal detection,feedback and reconstruction of channel state information,channel decoding,end-to-end wireless communication systems,the latest research progress of international academic circles in recent years was presented.On this basis,the development trend in the future was preliminarily forecasted.